(untitled) (African Journal of Law and Politics, 2023)
The influence of digitalisation on economic activities and other aspects of social life is no longer to be demonstrated. Digitalisation is crucial for computerisation of administrative procedures which is protuberant in the modern era. This is prominent especially during this period of Covid-19 pandemic whereby social distancing and confinement are the most prescribed barrier measures. Adopting electronic procedures in the functioning of the TPPCR and other means of decongesting it is timely. Through qualitative analysis, this paper reveals that though the OHADA lawmaker has open perspectives on computerisation of the commercial register, Cameroon has not taken any step to achieve it. This paper advises that even though reforms towards achieving the above may still face a lot of constraints, Cameroon is encouraged to accelerate the procedure of computerisation of the register, if it must implement barrier measures against Covid-19 at the level of TPPCR.